2012
DOI: 10.1016/j.fcr.2011.10.007
|View full text |Cite
|
Sign up to set email alerts
|

Effect of interseeding cover crops and fertilization on weed suppression under an organic and rotational cropping system

Abstract: Interseeding cover crops is an alternative to laborious intertillages and hand weeding followed in organic farming. The objective of this study was to evaluate the effect of fertilization and interseeding cover crops on the growth of main crops and weeds and the stability of weed suppression over years and main crop species under four-year rotational organic farming. Two cover crops, winter rye (Secale cereale L.) and hairy vetch (Vicia villosa Roth), were interseeded in furrows of potato (Solanum tuberosum L.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(31 citation statements)
references
References 27 publications
(35 reference statements)
1
30
0
Order By: Relevance
“…Uchino et al, (2009) resulted in increased coverage of corn, soybean and cover crop, declined weed dry matter. Weeds were suppressed effectively and stably without yield reductions of main crops by inter-seeded cover crops with sufficient fertilization in organic farming systems (Uchino et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Uchino et al, (2009) resulted in increased coverage of corn, soybean and cover crop, declined weed dry matter. Weeds were suppressed effectively and stably without yield reductions of main crops by inter-seeded cover crops with sufficient fertilization in organic farming systems (Uchino et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…The risk of weeds not only reducing crop yields but also decreasing the commercial quality and the feeding palatability of main crops and enhance the soil seed bank of weeds, which may cause continuous weed infestation of field crops (Uchino et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…In the presence of bean and soybean, intercepted light by velvetleaf reduced significantly. Uchino et al (2012) noted that light competition of main and cover crops with weeds affected the weed growth. The high leaf area index of maize, bean and soybean enhanced the ability of intercepting solar radiation by these plants and therefore decreased the absorbed light by velvetleaf (Poggio, 2005).…”
Section: Absorbed Light Densitymentioning
confidence: 99%
“…Our findings was in according to Vazin et al (2010) results. Uchino et al (2012) reported that LAI of weed decreased due to increasing of leaf area and growth of main crops and cover crops. The LAD of bean was higher than velvetleaf LAD at both planting dates (Figures 1a, 1d).…”
Section: Leaf Area Densitymentioning
confidence: 99%
See 1 more Smart Citation